Business plan: Recycling plant of post-industrial waste of the textile industry - Pereira, Luís Fernando Alves (2018)
Recycling is important in today’s world if we want to leave this planet for our future generations. In the last few decades, movements and trends have educated the general public to recycle, reduce and reuse its consumer products. However, despite the steps made in changing the mentality in the individual landscape, a big cog in the machine that churns out waste into this world still goes unchecked: the manufactures. The industry landfills millions of tons of textile fibers mainly because there are no incentives to reverse this trend. Once in landfills, natural fibers can take hundreds of years to decompose and release a plethora of toxic gases and substances. As such, textile recycling is a significant challenge to be addressed as we strive to move closer to a zero landfill society and a low resource use circular economy society. The development of this Business Plan intends to create a solution to this problem in the textile industry, more exactly the Portuguese textile Industry, and aims to assess the economic and financial feasibility, and market deployment of this innovative format and transform the Portuguese textile recycling industry. The aim is to feed the recycled raw materials, which traditional get reused - not recycled - into insolation material, back into the economy as a raw material to be used in innovative lines of environmentally friendly yarns, which consequently gets made into environmentally friendly fabric that can be used in most everyday products.